FDI spillovers at regional level : evidence from Portugal - Crespo, Nuno (2009)
This paper aims to establish whether geographical proximity between multinational and domestic firms is relevant to the occurrence of FDI spillovers, by considering both horizontal and vertical spillovers. Using data for Portugal, this hypothesis is confirmed. In the case of horizontal externalities, the impact is negative, probably due to the competition effect. Concerning vertical externalities, a positive impact through backward linkages is observed. Additionally, omission of the regional dimension provokes a bias on the estimation of the intra-sectoral effect at the national level. These results raise important implications for the economic policies aiming to attract FDI and promote regional development.